Effective school organizational communication management: Descriptive study at Madrasah Aliyah Negeri 1 Yogyakarta - Ayu Usada Rengkaningtias; Siswantoyo Siswantoyo (Informasi, 2022)
Organizational communication management determines the effectiveness of an educational institution. Good communication in educational organizations will make a school more effective. Conversely, without good organizational communication management, miscommunication often occurs. This article aims to analyze and describe organizational communication management at Madrasah Aliyah Negeri 1 Yogyakarta as one of the leading schools in the city of Yogyakarta. This study used descriptive qualitative method. The results of the study show that for superior schools, communication within the organization is vital in school management. As a top school, the management of MAN 1 Yogyakarta carries out various ways to improve achievement through organizational communication management. One of them is by creating a healthy flow of information for all components of the school. Leaders also innovate in the form of a special team that acts as a communication "bridge" that specifically handles and improves school performance. MAN 1 devotes all efforts to continuously improve school performance. This is because MAN 1 management assesses that achievement is a very important indicator of the quality and effectiveness of an educational institution.